Kewenangan PPATK Dalam Mencegah dan Memberantas Transaksi Keuangan Mencurigakan Hasil Tindak Pidana pada Perjudian Online - Ryan Purnama Putra; Merline Eva Lyanthi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
One factor to consider in efforts to enforce illicit online gambling laws is preventing the flow of money from online gambling. In the midst of the use of technology in banking transactions and online gambling, it is important to pay attention PPATK Policy in Terminating Money Laundering Transactions in Online Gamblingand the need for preventive efforts with the rise of online gambling itself makes It is necessary to do research related to the Authority of the Financial Services Authority in Blocking the Results of Online Gambling Transactions. This research aims to inform and understand PPATK's policy for stopping suspicious money laundering transactions in online gambling. The type of research used in this legal research is normative legal research. The approach method used in this research is the statutory approach method. The research results are that PPATK's policy in stopping suspicious money laundering transactions in online gambling is to stop transactions because there are indications of online gambling activity, coordinating with the police to accelerate online gambling activities, and PPATK is tasked with collecting and processing suspicious information related to money laundering in online gambling.